A critique of car-free day - Tang, Zhong Jie (2017)
Over the years, the invention of automotive vehicles has brought about convenience to our everyday lives. However the role of automotive as mode of transport has become so crucial in everybody’s life that what was meant to improve and develop a better society have now become a form of overreliance and the development of lazy habits within humans. The presence of automotive have not only reduced the lack of interaction between humans and the environment but they have also caused a great amount of damage and pollution to our environment. Usage of automotive would naturally emit greenhouse gases and particulate matter. These 2 chemicals and components are the major contributor to the cause of global warming. On top of that the presence of automotive has brought about the necessity to build highways thus causing issues like land scarcity to happen. With all these problems arising, world leaders have now joined forces and collaborated with one another to take a closer look into the usage of vehicle and thus resulting in the birth of Car-Free day. Different countries implemented the use of carfree day to combat different issues, such as pollution issue, land scarcity, traffic congestions as well taking back public spaces just to name a few. This critique is to determine if Car-free Sundays, especially in Singapore have been successful with its aim of reclaiming public spaces due to land scarcity and as well as educate the public on car-lite lifestyle. This critique also aims to assess the success of the Car-Free Sundays through public opinion, studies on the sentiment of the usage of car-lite measures like personal mobility devices (PMD’s) and other alternatives, safety regulations and issues on PMD’s and bicycles .To do so, the criteria to define the success of car-free Sunday would be to meet or align the results obtained to see if it matches the objectives as stated by the Urban Redevelopment Authority (URA) planner through interviews or it is even in the same direction as what URA has previously planned for. The data have been collected by means of on-site interviews. By analysing the data collected, it was found that the carlite message has been gradually integrating at a slow pace into the public daily life. Two of the few car-lite measures such as the usage of bicycle and PMD’s are one of the best alternate mode of transport to automotive. However knowledge on PMD’s still remains partially unclear to the public and many are still unsure of the use of PMD’s. The lack of publicity on car-free day event results in the slow dissipation of news and information and hence many of the public are still unaware of the presence of the car-free day event. The participants who cycle, skate or ride a PMD during the car-free day event often come into conflict with one another due to conflict of lane usage and safety regulations. The issue of lack of regulations and legislation guarding and ensuring the safe use of PMD still exist and much can be done to improve on this situation. Cycling and skating appear as the main events during the car free day.